Effect of steam explosion on phenolic compounds and antioxidant capacity in adzuki beans. (8th June 2020) - Cheng, Anwei; Hou, Chunyu; Sun, Jinyue; Wan, Fachun
Abstract: BACKGROUND: Steam explosion is increasingly being used in the food processing industry as an efficient pretreatment technology. It is currently being used to pretreat adzuki beans at a pressure of 0.25–1.0 Mpa for 30 s and 90 s. In this study, the total polyphenol (TP) content in adzuki beans, including free polyphenols (FP) and bound polyphenols (BP), and their antioxidant activity, were determined after steam explosion treatment. RESULTS: The results showed that steam explosion can form large cavities and intercellular spaces, which aid the release of polyphenols. After steam explosion, the FP, BP, and TP content increased. The antioxidant capacity of FP and BP also increased, which demonstrated that there was a positive correlation between the polyphenol content and antioxidant capacity. Compounds of FP and BP were further identified by high‐performance liquid chromatography (HPLC). Protocatechin was the main ingredient in FP and BP, and protocatechin was higher in FP. Isoquercetin only exists in FP, and caffeic acid only in BP. After steam explosion, an increase in the protocatechin, catechin, and epicatechin content was detected in FP and BP. The phenolic compound and antioxidant capacity yield was increased at a pressure of 0.25–0.75 Mpa, however it decreased at 1.0 Mpa. A pressure of 0.75 Mpa for 90 s is the optimal condition for polyphenol separation in adzuki beans. CONCLUSION: A proper and reasonable steam explosion can effectively increase the release of phenolics and enhance the antioxidant capacity in adzuki beans. © 2020 Society of Chemical Industry